Open Access to Knowledge Part 2: Sharing Your Research Data - Brunet, Mélanie; Hatherill, Jeanette; Ripp, Chantal (Université d'Ottawa | University of Ottawa, 2021)
Slides of the second webinar of a two-part series on sharing research results openly. This presentation aims to demystify the copyright status of research data and the application of open licences, best practices in data sharing and deposit, and what supports are available at the University of Ottawa to further these objectives.
Keywords: Open access; Copyright; Open licences; Research data management; Open data; Data repositories